Anatomical and Morphological study of the Heart's Chambers and valves in Iraqi ducks Anser platyrhuncha: دراسة تشريحة شكلية لتجاويف وصمامات القلب في البط المحلي - Hassan, Mohammed Senna; Mohammed, Razaq J. (The Iraqi Journal of Veterinary Medicine, 2019)
Twenty Iraqi ducks hearts ( 10 male and 10 female ) have been used for demonstration and illustration of heart's valves and chambers as well as anatomical and morphological site of view to explain what modifications had been take place for ducks heart to perform his normal life at the circumstances of high blood pressure and pulse rate. The heart which has distinctly pointed apex was built in simple manner located in a transparent taught heart pericardial sac. It was pyramidal in shape externally and has a longitudinal salcus passing to the right side, the anterior of the heart is divided into two unequal anterior chamber similar to those of mammalian hear .The heart valves are modified in order to minimize the fraction that occur as a result of high blood pressure and pulse rate of the duck heart , also the muscular trabeculae replace the chordate tendineae , which were present in the mammalian heart in order to minimize the fraction resulting from high pulse rate..